THE EFFECTIVENESS OF USING FOUR SQUARE WRITING METHOD IN TEACHING ANALYTICAL EXPOSITION TEXT WRITING - Marina, .; Marbun, Rismaya; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The purpose of the research was to find out the effectiveness of Four Square Writing Method in teaching analytical exposition text writing. This research used pre experimental one group pre-test post-test design. The writer used cluster random sampling in determining the sample of the research and XI MIA 1 was chosen. The data collection used writing test. The analysis of the students? results used t-test and effect size formulas. The findings showed that the t-test was higher than the ttable (13.15 > 2.750). The alternative hypothesis (Ha) ?the use of Four Square Writing Method in teaching analytical exposition text writing at the eleventh grade students is effective? was accepted. In addition, the effect size result was 2.24 (ES >0.80). Therefore, teaching analytical exposition text writing by using Four Square Writing Method was highly effective in improving students? writing achievement. Keywords : Four Square Writing Method, Analytical Exposition Text Abstrak : Tujuan dari penelitian ini adalah untuk mencari keefektifan metode Four Square Writing dalam pengajaran menulis teks eksposisi analitis. Penelitian ini menggunakan pre experimental dalam bentuk one group pre-test post-test desain. Penulis menggunakan sampel acak kelompok dalam menentukan sampel penelitian dan kelas XI MIA 1 terpilih. Data dikumpulkan melalui tes menulis. Analisis hasil siswa menggunakan rumus t-test dan efek size. Penemuan memperlihatkan nilai t-test lebih tinggi dari ttable (13.15 > 2.750). Hipotesis alternatif (Ha) ?penggunaan metode Four Square Writing dalam pengajaran menulis teks eksposisi analitis pada murid kelas sebelas adalah efektif? diterima. Sebagai tambahan, efek size perlakuan adalah 2.24 (ES >0.80). Oleh karena itu, pengajaran menulis teks eksposisi analitis menggunakan metode Four Square Writing sangat efektif dalam meningkatkan hasil kemampuan menulis siswa. Kata Kunci : Metode Four Square Writing, Teks Eksposisi Analitis